UV Spectrophotometric Methods for the Determination of Anti-diabetic Drugs - Gowri Sankar, D.; Rajendra Kumar, J.M.; Reddy, M.V.V.N. (Asian Journal of Chemistry, 2010)
Simple and sensitive UV spectrophotometric methods are developed for the determination of pioglitazone hydrochloride and rosiglitazone maleate in pure and pharmaceutical dosage forms. Methods obey Beer's law in the concentration range 5–30 μg/mL and 10–60 μg/mL exhibiting maximum absorption at 270 nm and 318 om respectively. These methods are extended to pharmaceutical preparations and there is no interference from any common pharmaceutical additives and diluents.